Risk analysis in a multilevel supply model - Escalante, Jesús (2019)
This research proposes stress tests to evaluate a set of hypothetical crisis scenarios linked with periods of greater volatility in a sample of commercial transactions among three companies from a multilevel supply model. The solution identifies cost-related levels of impact for a set of hypothetical scenarios associated with parameters such as levels of reliability and volatility in a risky time horizon.